A Review on Research Results of Beef Cattle Feed - Ristianto Utomo (Indonesian Center for Animal Research and Development, 2004)
Based on rumen degradation rate, concentrates are divided into : slow degraded energy feeds, fast degraded energy feeds, slow degraded protein supplements, and fast degraded protein supplements. This classification is important to synchronize the presence of nutrients in the rumen used to stimulate rumen microbes growth . Rumen microbes-can be used as protein supplements for the host . Protein content, digestibility, and biological value of rumen microbes are about 65%, 75-85%, and 80%, respectively . Rice straw as an agricultural by product has a low protein content of not more than 7%, low digestibility, thus in the digestive tract, in rumen, and particle changes in rumen require about 81 .67 hours, 62.69 hours, and 1 .62% per hours, respectively. Rice straw utilization as feed needs supplementation and quality and digestibility improvement in the form of physical, chemical, biological, or combined. The physical treatment aims at reducing particle size or cell swelling . Reducing particle size of roughage will increase the rate of passage in the rumen, increase consumption, decrease digestibility, and reduce milk fat, while sodium hydroxide treatment will increase digestibility up to 100% without nutrient increase, however it is dangerous to human life and a pollutant for the agriculture field. Rice straw treatment using ammonia increase its digestibility and its nutrient . The biological treatment was conducted to change rice straw structure by enzyme lignocellulase and increase protein content with microorganism. Basically, the concept of biological treatment is restricted composing, conservation, and predigesting to increase quality. Recently, many commercial products have been developed for rice straw biological treatment orienting at predigesting of cellulose. The application of physical, chemical, and or biological treatment for agricultural by product is as component for complete feed Key words: Rumen Microbes, supplementation, predigesting